Journalism and Jim Crow : White supremacy and the Black struggle for a new America - Forde, Kathy Roberts; Bedingfield, Sid; Lichtenstein, Alexander C. (History of communication., 2021)
"White publishers and editors used their newspapers to build, nurture, and protect white supremacy across the South in the decades after the Civil War. At the same time, a vibrant Black press fought to disrupt these efforts and force the United States to live up to its democratic ideals. Journalism and Jim Crow centers the press as a crucial political actor shaping the rise of the Jim Crow South. The contributors explore the leading role of the white press in constructing an anti-democratic society by promoting and supporting not only lynching and convict labor but also coordinated campaigns of violence and fraud that disenfranchised Black voters. They also examine the Black press's parallel fight for a multiracial democracy of equality, justice, and opportunity for all-a losing battle with tragic consequences for the American experiment. Original and revelatory, Journalism and Jim Crow opens up new ways of thinking about the complicated relationship between journalism and power in American democracy. Contributors: Sid Bedingfield, Bryan Bowman, W. Fitzhugh Brundage, Kathy Roberts Forde, Robert Greene II, Kristin L. Gustafson, D'Weston Haywood, Blair LM Kelley, and Razvan Sibii"--